RESEARCH ON LOW AND HIGH CYCLE FATIGUE BEHAVIOR OF NI-CR ALLOY UNDER DIFFERENT FREQUENCY AT ROOM TEMPERATURE - WU HaiLi; AN ChunXiang; YU Xiao; LU LianTao (Jixie qiangdu)
Low cycle fatigue test（0.1 Hz 0.3 Hz,10~3 10~5 cycles） and conventional high cycle fatigue test（150 Hz.10~4 10~7 cycles） and ultra-high cycle fatigue test（20 k Hz,10~5 10~9 cycles） were carried on Ni-Cr Alloy at room temperature.The results of the three forms fatigue test were compared,and the energy-life curve reduced by 3-parameters power function were fitted.The fractograph of specimens were investigated and analyzed with scanning electron microscope.The results show that the fatigue crack initiation sites change from multiple surface cracks to single surface crack,then to subsurface of specimen with decreasing the load amplitude.